Synthesis and characterization of magnetite/PLGA/chitosan nanoparticles. (11th September 2015) - Ibarra, Jaime; Melendres, Julio; Almada, Mario; Burboa, María G; Taboada, Pablo; Juárez, Josué; Valdez, Miguel A
Abstract: In this work, we report the synthesis and characterization of a new hybrid nanoparticles system performed by magnetite nanoparticles, loaded in a PLGA matrix, and stabilized by different concentrations of chitosan. Magnetite nanoparticles were hydrophobized with oleic acid and entrapped in a PLGA matrix by the emulsion solvent evaporation method, after that, magnetite/PLGA/chitosan nanoparticles were obtained by adding dropwise magnetite/PLGA nanoparticles in chitosan solutions. Magnetite/PLGA nanoparticles produced with different molar ratios did not show significant differences in size and the 3:1 molar ratio showed best spherical shapes as well as uniform particle size. Isothermal titration calorimetry studies demonstrated that the first stage of PLGA-chitosan interaction is mostly regulated by electrostatic forces. Based on a single set of identical sites model, we obtained for the average number of binding sites a value of 3.4, which can be considered as the number of chitosan chains per nanoparticle. This value was confirmed by using a model based on the DLVO theory and fitting zeta potential measurements of magnetite/PLGA/chitosan nanoparticles. From the adjusted parameters, we found that an average number of chitosan molecules of 3.6 per nanoparticle are attached onto the surface of the PLGA matrix. Finally, we evaluated the effect of surface charge of nanoparticles on a membrane model of endothelial cells performed by a mixture of three phospholipids at the air–water interface. Different isotherms and adsorption curves show that cationic surface of charged nanoparticles strongly interact with the phospholipids mixture and these results can be the basis of future experiments to understand the nanoparticles- cell membrane interaction.